FOOD AND FEEDING HABIT OF SPINY EEL MACROGNATHUS PANCALUS (HAM-BUCH) FROM UPPER ASSAM - ABUJAM, SANTOSHKUMAR SINGH; SINGH, SORAM JITEN; DAKUA, SANJAY; PASWAN, GOBIN; SAIKIA, A K; BISWAS, S P (Journal of the Inland Fisheries Society of India, 2021)
The lowest value (0.57±0.06) of relative length of gut (RLG) of M. pancalus was found in 15-20 cm whereas the highest values (0.60±0.08) in 7-11 cm group. Gastro somatic index (GSI) ranged from 0.68 ±0.20 (January) to 2.47±0.89 (July) for males while from 0.54 ± 0.19 (December) to 2.89 ± 1.05 (August) for female. Fullness of gut was recorded as 21.27% (full); 9.92% (¾ full); 15.72% (½ full); 13.27% (¼ full); 19.77% (nearly empty) and 23% (empty). The active feeding (full & ¾ full) was recorded during monsoon, moderate (1/2 full) during pre-monsoon, poor (1/4 full and nearly full) during post monsoon and negligible during winter seasons. Gut content analysis revealed that insects were annually contributing to an average of 45.65 %; miscellaneous items including algal and fish eggs were 22.16 %; zooplankton (15.58 %); sand and mud (8.44 %); crustacean (3.99 %); annelids (2.69 %), and molluscs (1.49 %) of the total intake of food. In juveniles, most preferred food item was zooplanktonic organism (49.25 %), followed by insect larvae (27.94 %). Similarly, in adults, the insect larvae (36.48 %) were consumed heavily followed by zooplankton (22.53%). The highest index of pre-ponderance was claimed by insect larvae followed by zooplankton, miscellaneous included unidentified matter, algal and fish egg, sand and mud, crustaceans, annelids, and molluscs. Key words: M. pancalus, RLG, fullness of gut, GSI, gut content analysis, index of pre-ponderance